2013
DOI: 10.1177/0193945913480275
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Influences of Early Childhood Obesity

Abstract: This study aims to determine the contributing factors for early childhood overweight/obesity within the contexts of the child's home, school, and community, and to determine how much each of the ecological contexts contributes to childhood overweight/obesity. The framework was developed from Bronfenbrenner's ecological systems theory. Data for 2,100 children from the Early Childhood Longitudinal Study, Birth Cohort, were used in a series of multilevel modeling analyses. There was significant variation in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
6
35
0
Order By: Relevance
“…Parental feeding style (23.4%) and family functioning (6.6%) contributed most to the variance in the BMI-z scores. These findings are consistent with a previous study analyzing national surveillance data, which reported that family-level factors (e.g., child's race and parents' highest education level) were the main contributing factors for childhood overweight/obesity (Boonpleng et al, 2013). Although family background factors have been associated with children's overweight/obesity in prior studies, none of the family background factors were found to be related to children's weight in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Parental feeding style (23.4%) and family functioning (6.6%) contributed most to the variance in the BMI-z scores. These findings are consistent with a previous study analyzing national surveillance data, which reported that family-level factors (e.g., child's race and parents' highest education level) were the main contributing factors for childhood overweight/obesity (Boonpleng et al, 2013). Although family background factors have been associated with children's overweight/obesity in prior studies, none of the family background factors were found to be related to children's weight in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Literature suggests these approaches should begin during the preschool years (aged 2–5 years) because adiposity rebound, the point of BMI increase after a minimal BMI, occurs during this period and may predict future obesity (Boonpleng et al. ). The preschool period is also a key developmental stage in which children learn and adopt healthy lifestyles (Doi et al.…”
Section: Introductionmentioning
confidence: 99%
“…The EST emphasizes the interactive influence of each system on child development making it a good fit for studies examining factors that contribute to childhood obesity (Boonpleng et al. ). It provides a comprehensive framework for a multilevel analysis of child, family, childcare setting and community variables that are likely to affect preschool children's weight status.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies examine impressive, evidence-based, integrated multilevel lists of contributors to childhood obesity, claiming to apply an ecological view (e.g. [8-10]). However, integration is not synonymous to interaction.…”
Section: Introductionmentioning
confidence: 99%